2014
DOI: 10.1039/c4cp00030g
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive simulations of the activation barrier to dissolution of amorphous silica in water

Abstract: Molecular dynamics simulations employing reactive potentials were used to determine the activation barriers to the dissolution of the amorphous SiO2 surface in the presence of a 2 nm overlayer of water. The potential of mean force calculations of the reactions of water molecules with 15 different starting Q4 sites (Qi is the Si site with i bridging oxygen neighbors) to eventually form the dissolved Q0 site were used to obtain the barriers. Activation barriers for each step in the dissolution process, from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 46 publications
(87 reference statements)
10
51
0
Order By: Relevance
“…By using the dissociative watersilica potential developed by Mahadevan and Garofalini, 53 it was found that among the four (Q 4 → Q 3 , Q 3 → Q 2 , Q 2 → Q 1 , or Q 1 → Q 0 ) reactions, the Q 3 → Q 2 and Q 2 → Q 1 reactions have the highest activation energy of~14.1 kcal/mol, and is the rate limiting step in bulk silica dissolution. 19,24 These barriers are in the lower range of the experimental energy barriers of 14-24 kcal/mol and below values from cluster-based ab initio calculations (18-39 kcal/ mol). 19,24 Similar differences in energy barriers for siloxane bond breakage were identified by Du and de Leeuw on quartz surfaces.…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 97%
See 2 more Smart Citations
“…By using the dissociative watersilica potential developed by Mahadevan and Garofalini, 53 it was found that among the four (Q 4 → Q 3 , Q 3 → Q 2 , Q 2 → Q 1 , or Q 1 → Q 0 ) reactions, the Q 3 → Q 2 and Q 2 → Q 1 reactions have the highest activation energy of~14.1 kcal/mol, and is the rate limiting step in bulk silica dissolution. 19,24 These barriers are in the lower range of the experimental energy barriers of 14-24 kcal/mol and below values from cluster-based ab initio calculations (18-39 kcal/ mol). 19,24 Similar differences in energy barriers for siloxane bond breakage were identified by Du and de Leeuw on quartz surfaces.…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 97%
“…19,24 These barriers are in the lower range of the experimental energy barriers of 14-24 kcal/mol and below values from cluster-based ab initio calculations (18-39 kcal/ mol). 19,24 Similar differences in energy barriers for siloxane bond breakage were identified by Du and de Leeuw on quartz surfaces. 67 Understanding how the local environment alters stability of siloxane bonds is critical to understanding how silica dissolves.…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…use of a reactive potential is critical for analyzing all the reactions and material transport inside the glass and solution. Recent improvements of reactive MD force fields have allowed for several advances in the modeling of silica‐water interactions . In one of the most recent studies of sodium silicate hydration with the ReaxFF, leaching of sodium into water and accumulation at the interface of the leached Na + ions was observed along with proton transport inside the glass in the first nanosecond of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Above 600°C, 100S undergoes extensive condensation of the Si-OH located at surface of the pores leaving the silica network exclusively composed of Q 4 species, whereas at 500°C (used here) a mixture of Q 2 ; Q 3 and Q 4 species was obtained [26,29,30]. When 100S was stabilised above 600°C, an activation energy barrier of 14-24 kcal mol À1 had to be crossed for the hydroxylation of the Q 4 species to occur prior to the release of silica, which in turn slowed down the dissolution [52][53][54].…”
Section: Effect Of the Crystallisation On The In Vitro Performancementioning
confidence: 99%